SALT HYDROLYSIS TEACHING METHODOLOGY IN THE HIGHER EDUCATION SYSTEM (Proceedings of International Conference on Educational Discoveries and Humanities, 2023)
Today, in the school chemistry course and in the higher education system , the teaching of the processes that go through the hydrolysis of salts leads to the study of the mechanism of any chemical reactions . This is formed by explaining the mechanism of hydrolysis of salts to students and students, after the substance is dissolved in the solvent . It is also possible to explain electrolysis, hydrolysis, amphotericity, electrical conductivity, electrode potentials, oxidation-reduction processes based on this theory [1].